Patterns of public and private maternal healthcare use among the urban poor of Bangladesh: cross-sectional survey - Shafayatul Islam Shiblee; Harun ur Rashid (Bangabandhu Sheikh Mujib Medical University Journal)
Background: Despite some progress, in Bangladesh access to high quality essential maternal healthcare remains inadequate.  Women living in urban slums may face additional obstacles to maternal healthcare, but evidence remains limited. The study aims to explore the patterns of maternal healthcare utilisation in urban slums.